Reconnaissance of tumor immune microenvironment spatial heterogeneity in metastatic renal cell carcinoma and correlation with immunotherapy response. (9th February 2021) - Hajiran, A.; Chakiryan, N.; Aydin, A. M.; Zemp, L.; Nguyen, J.; Laborde, J. M; Chahoud, J.; Spiess, P. E; Zaman, S.; Falasiri, S.; Fournier, M.; Teer, J. K; et al.
Summary: A clearer understanding of the tumor immune microenvironment (TIME) in metastatic clear cell renal cell carcinoma (ccRCC) may help to inform precision treatment strategies. We sought to identify clinically meaningful TIME signatures in ccRCC. We studied tumors from 39 patients with metastatic ccRCC using quantitative multiplexed immunofluorescence and relevant immune marker panels. Cell densities were analyzed in three regions of interest (ROIs): tumor core, tumor–stroma interface and stroma. Patients were stratified into low‐ and high‐marker density groups using median values as thresholds. Log‐rank and Cox regression analyses while controlling for clinical variables were used to compare survival outcomes to patterns of immune cell distributions. There were significant associations with increased macrophage (CD68 + CD163 + CD206 + ) density and poor outcomes across multiple ROIs in primary and metastatic tumors. In primary tumors, T‐bet + T helper type 1 (Th1) cell density was highest at the tumor–stromal interface ( P  = 0·0021), and increased co‐expression of CD3 and T‐bet was associated with improved overall survival ( P  = 0·015) and survival after immunotherapy ( P  = 0·014). In metastatic tumor samples, decreased forkhead box protein 3 (FoxP3) + T regulatory cell density correlated with improved survival after immunotherapy ( P  = 0·016). Increased macrophage markers and decreased Th1 T cell markers within the TIME correlated with poor overall survival and treatment outcomes. Immune markers such as FoxP3 showed consistent levels across the TIME, whereas others, such as T‐bet, demonstrated significant variance across the distinct ROIs. These findings suggest that TIME profiling outside the tumor core may identify clinically relevant associations for patients with metastatic ccRCC. Abstract : A better understanding of the tumor immune microenvironment may serve as a critical step in advancing precision treatment strategies. We analyzed tumors from patients with metastatic clear cell renal cell carcinoma using quantitative multiplexed immunofluorescence and relevant immune cell markers in three separate regions of interest. Our results demonstrate that patterns of immune cell spatial distribution across microenvironment compartments in primary and metastatic tumors correlate with meaningful clinical outcomes.